Efficiency of Microfinance (MF) Institutions in Bangladesh: A Study on Top 10 MF Institutions - Afroze, Dilruba; Salehin, Md Riad Us (International Journal of Business, Economics and Management, 2020)
Bangladesh has been referred to as “the birthplace (and sometimes as the 'Mecca') of microfinance all over the world. However, there are very few studies that investigate the efficiency of this industry. This paper aims to find the efficiency of the top 10 (in terms of market share) Microfinance Institutions (MFIs) of Bangladesh. The data were collected from secondary sources and annual reports of the 10 MFIs were used extensively. Data Envelopment Analysis (DEA) method was used to measure the efficiency of those MFI and regression analysis to test the hypothesis. The DEA method measures efficiency by analyzing the inputs and outputs. The inputs for this paper were the number of employees (NE), Fixed Asset (FA) and Operating Expenses (OE) of each MFI. Based on these inputs, DEA measures the efficiency by comparing the outputs. The outputs were the amount of Loan Outstanding (LO) and Deposits of Members (DM) of each firm. This method not only measures the efficiency but also provides recommendation to minimize the inputs and maximize the outputs. The result of this study reveals that only 30% of the top 10 MFIs are operating with their full potential and their average efficiency rate is 65.5%. MFIs that are not operating under their optimal size, they have a 94.9% of average efficiency rate. However, it was found that in terms of collecting deposits, 60% of the top 10 MFIs are efficient whereas, only 10% are efficient in terms of disbursing loans.